Genel liselerde okul güvenliği algılarının incelenmesi - Geyin, Çiğdem (My University, 2007)
GENEL LİSELERDE OKUL GÜVENLİĞİ ALGILARININ İNCELENMESİ ÖZET Araştırma eğitimcilerin ve öğrencilerin görüşleri bağlamında genel liselerdeki okul güvenliği algılarını belirlenmek amacıyla gerçekleştirilmiştir. Araştırma tarama türünde olup, okulların güvenliğini ölçme amacına yönelik veriler araştırmacı tarafından geliştirilen Eğitimciler Okul Güvenliği Ölçeği ve Öğrenciler Okul Güvenliği Ölçeği kullanılarak elde edilmiştir. Ölçekler 5’er alt boyuttan oluşmaktadır. Eğitimciler Okul Güvenliği Ölçeği toplam Cronbach Alpha değeri 0,941, Öğrenciler Okul Güvenliği Ölçeği toplam Cronbach Alpha değeri 0,902’dir. Araştırma İstanbul ili Anadolu yakasında tesadüfi olarak seçilen Kartal, Kadıköy, Maltepe, Pendik, Üsküdar ilçelerindeki 10 genel lisede 194 eğitimci ve 1420 öğrenci ile 2006-2007 öğretim yılında gerçekleştirilmiştir. Verilerin analizinde Pearson Çarpım Moment Korelasyon Analizi, İlişkili Grup T Testi, İlişkisiz Grup T Testi, Mann Whitney-U Analizi, Tek Yönlü Varyans Analizi (ANOVA), Kruskal Wallis-H Analizi, Scheffe, LSD ve Tamhane’s T2 istatistik teknikleri kullanılmıştır. Anlamlılık düzeyi .05 olarak alınmıştır. Araştırma sonunda: (1)Eğitimcilerin son bir yılda okulda yaşadıkları en önemli güvenlik problemleri sırasıyla öğrencilerin çakı, bıçak gibi tehlikeli cisimler bulundurması, okul içi öğrenci kavgası, vd. olarak belirlenirken, öğrencilerin son bir yılda okulda yaşadıkları en önemli güvenlik problemleri sırasıyla gasp (hırsızlık), okul içi öğrenci kavgası, şakayla karışık silahla tehdit etme, vd. olarak belirlenmiştir. (2)Okulların güvenliği ile ilgili eğitimcilerin algılarının görev, cinsiyet, görev yapılan okulun öğrenci mevcudu, kıdem, mezuniyet, branş, okulda güvenlik ile ilgili hizmet içi eğitim faaliyetine katılmaları değişkenlerine göre Eğitimciler Okul Güvenliği Ölçeği alt boyutlarında anlamlı şekilde farklılıklaştığı belirlenmiştir. (3)Okulların güvenliği ile ilgili öğrencilerin algılarının cinsiyet, öğrenim gördükleri sınıf, öğrenim gördükleri alan, annelerinin ve babalarının eğitim durumu değişkenlerine göre anlamlı şekilde farklılaştığı belirlenmiştir. RESEARCHING THE PERCEPTION OF SCHOOL SAFETY IN GENERAL HIGH SCHOOL

The research was carried out to determine the perceptions of school safety in general high schools within the context of the ideas of educationists and the students. The survey was a scanning type one and the data which were used to measure the safety of schools were obtained by using Educationists School Safety Scale and Students School Safety Scale which were built up by the researcher. Scales were made up of 5 sub-dimensions. The total Cronbach Alpha Value of Educationists School Safety Scale was 0,941 and the total Cronbach Alpha Value of Students School Safety Scale was 0,902. The survey was carried out within 2006-2007 educational year, in İstanbul Anatolian Side in 10 general high schools which were randomly chosen in Kartal, Kadıköy, Maltepe, Pendik, Üsküdar Districts and with the participation of 194 educationists and 1420 students. In the analysis of the data, Pearson Analysis of Multiplication Moment Correlation, Paired Samples T Test, Independent Sampels T Test, Mann Whitney-U Analysis, One Way Factor Analyis (ANOVA), Kruskal Wallis-H Analysis, Scheffe, LSD and Tamhane’s T2 statical techniques were used. The significance level was taken as 0.5. At the end of the survey: (1)The most important safety problems which the educationists experienced within the previous year were in order, the students’ carrying dangerous items such as knife and jackknife, student fights within the school etc., and the most important safety problems which the students experienced within the previous year were in order, hijacking (theft), student fights within the school, threatening with weapons by kidding etc. (2)It was identified that the safety of schools according to educationists perceptions differentiate in a meaningful way some sub-dimensions to variables of the duty, the sex, the population of the school which is worked, seniority, graduation, branch and in service education about safety in school variety. (3)It was identified that the safety of schools according to the students’ perceptions differentiate in a meaningful way some sub-dimensions to variables of the sex, the classes which they are educated, the field which they are educated and their parents’ educational situations. It has been proposed suggestions for people who are arranging the educational policies to provide safety in schools, school administrations, educationists, researchers and society.
Keywords: Eğitim Denetimi; Liseler_Okul Güvenliği